If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 12) = 101 + -200x Reorder the terms: 5(12 + x) = 101 + -200x (12 * 5 + x * 5) = 101 + -200x (60 + 5x) = 101 + -200x Solving 60 + 5x = 101 + -200x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '200x' to each side of the equation. 60 + 5x + 200x = 101 + -200x + 200x Combine like terms: 5x + 200x = 205x 60 + 205x = 101 + -200x + 200x Combine like terms: -200x + 200x = 0 60 + 205x = 101 + 0 60 + 205x = 101 Add '-60' to each side of the equation. 60 + -60 + 205x = 101 + -60 Combine like terms: 60 + -60 = 0 0 + 205x = 101 + -60 205x = 101 + -60 Combine like terms: 101 + -60 = 41 205x = 41 Divide each side by '205'. x = 0.2 Simplifying x = 0.2
| -8x-10=0 | | 2(4x+8)=-40 | | 7(-8-3x)=-266 | | -2(-1x+10)=-20 | | 3(4-2x)=78 | | 5x-6y=34 | | -3(-6x+9)=153 | | 7(-1x-3)=-35 | | 3y+2x=16 | | 7(1-5x)=-343 | | 69*.10= | | 5(4x+7)=55 | | 11+(-2)= | | 7(6x-3)=273 | | X^2+y^2-xy=7 | | c^2=2c^2+99 | | 3x+4y=66 | | 5+5x=-2x-44 | | 24=-16t^2+32t+6 | | 6x+10=-2x+34 | | 3+7x=6x-3 | | -5+(5)= | | 6x^2y^2/9x | | -1/4x+12 | | 7x+4=39+2x | | 76b^2=19 | | (3x-2x)(2x+5)=0 | | x-1=-16+6x | | -2-5x-x=-2 | | 2(-14+-3y)-4y=-30 | | 2-2x+7x=42 | | 21=x+2x+9 |